A seroepidemiological study across age groups before and after the 2010–2011 mumps epidemic in Japan. Issue 11 (18th July 2022) - Morino, Saeko; Satoh, Hiroshi; Arai, Satoru; Suzuki, Motoi; Tanaka‐Taya, Keiko
Abstract: In Japan, large‐scale mumps epidemics recur every 4–6 years because of low vaccination coverage. This study aimed to describe the seroprevalence of mumps in the Japanese population and identify the age groups most affected. The prevalence of anti‐mumps antibodies was evaluated based on 1000 serum samples obtained from the Japanese National Serum Reference Bank. These samples consisted of 50 sera for each of 10 different age groups, collected during 2007–2008 (pre‐epidemic period) and 2012–2013 (post‐epidemic period). Seropositivity was lowest in the 6–11 months subgroup (3% and 0% in pre‐ and post‐epidemic periods, respectively) and highest in the 10–14 years group (66% and 72% in pre‐ and post‐epidemic periods, respectively). A comparison of anti‐mumps antibody prevalence throughout the two periods considered revealed a large rise in seropositivity among the 2004–2008 birth cohort, using that of the 1–4 years group as representative in the pre‐epidemic period (from 22% in pre‐ to 58% in post‐epidemic periods;  p  = 0.0002). These results indicate that most people likely gain antibodies to the mumps virus during their childhood, especially during the first epidemic that they experience after their second year of life. Therefore, children should be vaccinated against mumps soon after their first birthday for effective prevention.